Settlement of Problematic Loans in the Unit Pengelola Kegiatan (UPK) of Pidie District did Sharia - Nufiar; Mariana; Muhammad Ali (Syntax Corporation Indonesia, 2020)
This research aims to determine the cause of problematic credit in UPK Pidie district and problematic credit settlement procedures in UPK Pidie District as well as the settlement of problematic credit on UPK in Pidie district according to Sharia. Results of the study showed that the main factor of the cause of problematic credit in the UPK of Pidie District is because of business and business results that do not match the expectations plus more household needs that are increasingly increasing the day, earnings that do not meet the needs. Also and credit given is not fully used for capital, there are groups using loans for household needs. The problematic credit settlement procedure for UPK Pidie District is by conducting a field review, conducting coaching many times by continuing to spur the group to pay by the next set time with restructuring efforts. The settlement of problematic credit in the UPK Pidie District is appropriate because the UPK does not attract the angling but always takes a family path with the affected group members.